Effects of Sex and Diet on Gut Microbiota of Farmland-Dependent Wintering Birds - Liu, Gang; Meng, Derong; Gong, Minghao; Li, Huixin; Wen, Wanyu; Wang, Yuhang; Zhou, Jingying (Frontiers in Microbiology, 2020)
Gut microbiota plays an important role for bird biological and ecological properties, and sex and diet may be important intrinsic and extrinsic factors influencing gut microbial communities. However, sex difference of gut microbiota has been rarely investigated in free-living birds, and it remains unclear how sex and diet interactively affect avian gut microbiota composition and diversity, particularly under natural conditions. Here we used non-invasive molecular sexing technique to sex the fecal samples collected from two wintering sites of Great Bustard, which is the most sexually dimorphic among birds, as well as a typical farmland-dependent wintering bird. High-throughput sequencing of 16S was applied to identify the gut microbiota communities for both sexes under two diets (wheat_corn and rice_peanut). The results showed that 9.74% of common microbiota taxa was shared among four groups (sex vs. diet), revealing the conservatism of gut microbiota. Microbiota diversity, composition and abundance varied on different diets for male and female Great Bustards, suggesting that the gut microbiota was interactively influenced by both sex and diet. Under the wheat_corn diet, females had higher abundances of the phylum Verrucomicrobia than males, but lower Bacteroidetes and Firmicutes compared to males; meanwhile, the microbiota diversity and evenness were higher for males than females. In contrast, under the rice_peanut diet, females were more colonized by the phylum Firmicutes than males, but less by the phylum Bacteroidetes; while males had lower microbiota diversity and evenness than females. This study investigated the impacts of sex and diet on microbiota of Great Bustards, and highlights the need of new studies, perhaps with the same methodology, taking into account bird ages, flock size, breeding or health status, which will contribute to the understanding of ecology and conservation of this vulnerable species.